Way better than the original!! Music video covers and language revitalisation: A sociosemiotic view - Dlanske, Kati (Apples - Journal of Applied Language Studies, 2016)
The development of the social media has opened up new spaces and genres for minoritised languages. As argued in previous research, access to new media spaces can contribute to the revitalisation of minoritised languages by generating new functions and values for them. Combining sociolinguistic and sociosemiotic approaches and bringing together data from four minority language contexts, Irish, Welsh, Sámi, and Corsican, this study addresses the potential of music video covers on YouTube to contribute to language revitalisation. The investigation suggests that music video covers in minority languages can have significance in language revitalisation in both language ideological and practical terms. However, these effects are not just a matter of access to a new media space (YouTube) or a new genre (music video cover) but, in a much more complex manner, a question of practices of relocalisation and the semiotic resources used. As semiotic aggregates, music video covers can not only endow minority languages and their speakers with a new glamour, but also recirculate and reinforce old, stereotypical notions. While ‘new glamour’ may be desirable, the study points, on the other hand, to the need for critical interrogation of the terms on which minority languages are commodified in the context of contemporary media culture.